Splines and PDEs : from approximation theory to numerical linear algebra : Cetraro, Italy 2017 /: from approximation theory to numerical linear algebra : Cetraro, Italy 2017. (2018) - Kunoth, Angela, 1963-; Lyche, Tom; Sangalli, Giancarlo; Serra-Capizzano, Stefano
No abstract available